Preventive logistics and its role in supply chain management - M. M. Begichev; A. V. Vlasov; A. I. Panshin (Путеводитель предпринимателя, 2022)
In modern economic and political conditions, the main task of Russia is to fully realize its foreign economic potential, which means an increase in the efficiency of foreign economic transit. The development of the logistics potential of the Russian Federation is of paramount importance not only for the transport area of the state, but also for geopolitics, the economy in general, and the social sphere.For a progressive increase in economic indicators in the freight transit of the Russian Federation, there is one «bottleneck» — at present, the state of the transport infrastructure — in most regions of Russia, it is completely impossible to ensure the necessary efficiency of transit freight traffic, thus there is a need to competently form the transport and logistics infrastructure and clearly identify where problems may arise and prepare the necessary solutions in advance.